Atropopeptides are a Novel Family of Ribosomally Synthesized and Posttranslationally Modified Peptides with a Complex Molecular Shape. Issue 41 (7th September 2022) - Nanudorn, Pakjira; Thiengmag, Sirinthra; Biermann, Friederike; Erkoc, Pelin; Dirnberger, Sabrina D.; Phan, Thao N.; Fürst, Robert; Ueoka, Reiko; Helfrich, Eric J. N.
Abstract: Biomacromolecules are known to feature complex three‐dimensional shapes that are essential for their function. Among natural products, ambiguous molecular shapes are a rare phenomenon. The hexapeptide tryptorubin A can adopt one of two unusual atropisomeric configurations. Initially hypothesized to be a non‐ribosomal peptide, we show that tryptorubin A is the first characterized member of a new family of ribosomally synthesized and posttranslationally modified peptides (RiPPs) that we named atropopeptides. The sole modifying enzyme encoded in the gene cluster, a cytochrome P450 monooxygenase, is responsible for the atropospecific formation of one carbon‐carbon and two carbon‐nitrogen bonds. The characterization of two additional atropopeptide biosynthetic pathways revealed a two‐step maturation process. Atropopeptides promote pro‐angiogenic cell functions as indicated by an increase in endothelial cell proliferation and undirected migration. Our study expands the biochemical space of RiPP‐modifying enzymes and paves the way towards the chemoenzymatic utilization of atropopeptide‐modifying P450s. Abstract : Atropopeptides are a family of ribosomally synthesized and postranslationally modified peptides with an unusual complex molecular shape. A single cytochrome P450 is sufficient for the atropospecific introduction of one carbon‐carbon and two carbon‐nitrogen bonds. A two‐step maturation process yields hexa‐ and pentapeptide products that act as signaling metabolites and show proliferative and pro‐migratory properties in endothelial cell cultures.